Fotografía y dictaduras: estrategias comparadas entre Chile, Uruguay y Argentina. - Cora Gamarnik (Nuevo mundo - Mundos Nuevos, 2012)
The article proposes a comparative analysis of some of the uses of press photography in the dictatorships of Chile, Uruguay and Argentina, and the attempts to fight them basing on the actions and images of some groups of photographers. The hypothesis which got us started is that the three dictators shared the same communication strategy, a kind of “Operation Condor” for the dictatorial propaganda led by experts in what they called “psychological action”. This paper will show how photojournalists emerged in the three countries and, still at risk, used photography as a tool to confront that dominant visual discourse. In both Chile and Argentina, they organized collectively in order to break with the isolation and individualism, and therefore they managed to create a vital attitude capable of expressing the conflict and the diversity of societies which dictatorships tried to discipline, intimidate and blend. The images they left us also show that creativity and innovation in photography were not defeat; on the contrary, they were reappearing after state terrorism with more strength, vitality and imagination than ever before.